A typology for Antarctic futures. Issue 1 (2nd January 2019) - Frame, Bob
ABSTRACT: This research note places interest in the long-term future of Antarctica in a historical context. It then examines the historical development of thinking about the long-term future of Antarctica over time using a typology of scenarios often used by researchers in futures studies, namely extrapolatory studies, back-casting, exploratory studies and integral futures. This covers work from the biophysical sciences, social sciences and the humanities. Drawing on literary works as well as research publications, this research note aims to provide a tentative structure in which Antarctic futures can be further developed and explored. It should be of benefit for those engaged in research, those involved in the management of Antarctic programmes, and those responsible for developing Antarctic policy. The paper concludes that meaningful debate about the future of the continent can be accelerated through the active development of futures literacy within the Antarctic research and management communities for improved policy outcomes.